Hydroxyapatite coatings for biomedical applications - Zhang, Sam. (Advances in materials science and engineering (Boca Raton, FL), 2013)
"This handbook covers developments in processing and property characterization and applications of Hydroxyapatite (HA), providing a timely resource for active researchers and newcomers to the field. It details HA coatings and use in dental implants, biomimetic HA materials, electrochemical and pulsed laser deposition, drug delivery, and more. In an approach that differs from traditional handbooks, it contains more than just data such as tables and figures. It is written in such a way that seasoned professionals at every level will find it a valuable data source that gives them indispensable help in their research"--